Elucidating the Chrononutrition Patterns and Sleep Quality Among Subfertile Patients With Different Vitamin D Levels - Sofwatul Mokhtarah Maluin; Norsham Juliana Nordin; Muhammad Shamsir Mohd Aris; Nurshahida Lokman; Afiqah Nadhirah Roslan; Juliana Yusof; Akmal Hisyam Arshad; Nur Islami Mohd Fahmi Teng (Springer Nature, 2025)
Indexed by Scopus and ERA (TIER 1)